Promotional effect of Mo addition on CoOX/Ti-Ce catalyst for oxidation removal of elemental mercury in flue gas. (15th July 2018) - Li, Honghu; Wang, Yuan; Wang, Shengkai; Wang, Xu; Hu, Jiangjun
Graphical abstract: Highlights: CoMo5/TiCe showed good performance on simultaneous oxidation of Hg 0 and NO. An interaction between Co and Mo promoted the activity of catalyst. Hg 0 oxidation by HCl over CoMo5/TiCe followed the Eley-Rideal mechanism. The deactivation effect of SO2 was reduced by Mo addition. Abstract: To enhance the catalytic activity for elemental mercury (Hg 0 ) oxidation and SO2 resistance of catalyst, Mo was applied to modify the CoOX /Ti-Ce (Co/TiCe) catalyst for better performance. The results showed that CoMo5/TiCe had the highest activity for Hg 0 oxidation in the wide temperature window of 100–400 °C in the presence of 10 ppm HCl and 6% O2 . NO exhibited insignificant effect on Hg 0 oxidation. SO2 and H2 O were found to inhibit Hg 0 oxidation. Hg 0 oxidation by HCl over CoMo5/TiCe catalyst mainly occurred through the Eley-Rideal mechanism, where gas-phase or weakly-bonded Hg 0 reacted with surface chlorine species originated from adsorbed HCl to form Hg 2+ . SO2 could obstruct the generation of surface active chlorine species, thus inhibiting Hg 0 oxidation. Compared with Co/TiCe, CoMo5/TiCe showed better resistance to SO2 and H2 O for Hg 0 oxidation. In the presence of 200 ppm SO2, CoMo5/TiCe achieved Hg 0 oxidation efficiency of 96.1% and a simultaneous NO conversion efficiency of 42.9% at 300 °C, showing better performance than Co/TiCe. The physicochemical properties of the catalysts were examined by BET, XRD, Ranman spectroscopy, H2 -TPR, XPS and EDS techniques to reveal the effect of Mo addition on the catalytic performances. It was found that an interaction of Mo with Co promoted the dispersion of Co3 O4, increased the Co 2+ and Oα concentration and enhanced the reducibility of catalyst, which contributed to the improvement of Hg 0 oxidation activity. Moreover, the SO2 resistance of catalyst was enhanced by suppressing the reaction between the catalyst and SO2 due to Mo addition.